Pengurusan Jenazah dalam Pandangan Hadis: Studi Takhrij dan Syarah Hadis - Kholid Nurrohman (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about the management of the dead in the view of hadith. This research uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about funeral arrangements in Muslim's narration No.1527. The results and discussion of this research show that the status of the hadith is hasan li ghairihi which meets the qualifications of practicing Islam. This study concludes that the Hadith narrated by Muslim No. 1527 is relevant to be used as a practice in the management of the dead.